The impact of daytime napping on athletic performance - A narrative review - Botonis, P. G.; Koutouvakis, N.; Toubekis, A. G. (Scandinavian Journal of Medicine & Science in Sports, 2021)
Mid-day napping has been recommended as a countermeasure against sleep debt and an effective method for recovery, regardless of nocturnal sleep duration. Herein, we summarize the available evidence regarding the influence of napping on exercise and cognitive performance as well as the effects of napping on athletes` perceptual responses prior to or during exercise. The existing studies investigating the influence of napping on athletic performance have revealed equivocal results. Prevailing findings indicate that following a normal sleep night or after a night of sleep loss, a mid-day nap may enhance or restore several exercise and cognitive performance aspects, while concomitantly provide benefits on athletes` perceptual responses. Most, but not all, findings suggest that compared to short-term naps (20-30 min), long-term ones (>35-90 min) appear to provide superior benefits to the athletes. The underlying mechanisms behind athletic performance enhancement following a night of normal sleep or the restoration after a night of sleep loss are not clear yet. However, the absence of benefits or even the deterioration of performance following napping in some studies is likely the result of sleep inertia. The present review sheds light on the predisposing factors that influence the post-nap outcome, such as nocturnal sleep time, mid-day nap duration and the time elapsed between the end of napping and the subsequent testing, discusses practical solutions and stimulates further research on this area.